Development of Domino Card Media in Early Childhood Counting Materials at the Pembina Metro East State Kindergarten, - Cahyo, Edo Dwi; Ardhana, Abeliza Galuh Tegar Ayu (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
The development of domino card media at the Pembina Metro East Kindergarten was carried out because several students were not able to say the numbers 1-10 in sequence. This problem is seen when children shout out numbers together, but have difficulty when asked to name the numbers one by one. Apart from that, some children also have low numeracy skills. Teachers usually start by writing numbers without introducing symbols. This research aims to produce domino card-based learning media, testing its feasibility and effectiveness in improving the numeracy skills of young children. Using the Research and Development (R&D) method with the ADDIE model, this research went through the stages of Analysis, Design, Development, Implementation and Evaluation. The validation results show that the domino card media is very feasible. Validation by media and material experts provided a high percentage, while trials with teachers and students also produced positive results. Thus, it can be concluded that this domino card media is effective in helping develop the numeracy skills of young children.